Surface-engineered polyethyleneimine-modified liposomes as novel carrier of siRNA and chemotherapeutics for combination treatment of drug-resistant cancers - Livia P. Mendes; Can Sarisozen; Ed Luther; Jiayi Pan; Vladimir P. Torchilin (Taylor & Francis Group, 2019)
Modification of nanoparticle surfaces with PEG has been widely considered the gold standard for many years. However, PEGylation presents controversial and serious challenges including lack of functionality, hindered cellular interaction, allergic reactions, and stimulation of IgM production after repetitive dosing that accelerates blood clearance of the nanoparticles. We report the development of novel liposomal formulations surface-modified with a low molecular weight, branched polyethyleneimine (bPEI)-lipid conjugate for use as an alternative to PEG. The formulations had very good stability characteristics in ion- and protein-rich mediums. Protein adsorption onto the liposomal surface did not interfere with the cellular interaction. bPEI-modified liposomes (PEIPOS) showed enhanced association with three different cell lines by up to 75 times compared to plain or PEGylated liposomes and were without carrier toxicity. They also penetrated the deeper layers of 3D spheroids. Encapsulating paclitaxel (PTX) into PEIPOS did not change its main mechanism of action. PEIPOS complexed and intracellularly delivered siRNAs and downregulated resistance-associated proteins. Finally, tumor growth inhibition was observed in a mouse ovarian xenograft tumor model, without signs of toxicity, in animals treated with the siRNA/PTX co-loaded formulation. These complex-in-nature but simple-in-design novel liposomal formulations constitute viable and promising alternatives with added functionality to their PEGylated counterparts.